1995
DOI: 10.1073/pnas.92.14.6239
|View full text |Cite
|
Sign up to set email alerts
|

A transgene coding for a human insulin analog has a mitogenic effect on murine embryonic beta cells.

Abstract: We have investigated the mitogenic effect of three mutant forms of human insulin on insulin-producing f3 cells of the developing pancreas. We examined transgenic embryonic and adult mice expressing (i) Insulin is a peptide hormone that plays a crucial role in the control of blood glucose. It contains two separate polypeptide chains, the A chain containing 21 amino acid residues and the B chain containing 30 residues, which are linked to each other by a pair of disulfide bonds (1). Insulin is synthesized by ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…It is possible that the use of B10-insulin may have been another factor. This insulin is superior to normal insulin in biological activity [29] and has some mitogenic properties [3032]. However, there was no evidence of excessive mitogenic activity or tumour development, while liver function tests remained normal throughout, with no lymphocytic infiltrates.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the use of B10-insulin may have been another factor. This insulin is superior to normal insulin in biological activity [29] and has some mitogenic properties [3032]. However, there was no evidence of excessive mitogenic activity or tumour development, while liver function tests remained normal throughout, with no lymphocytic infiltrates.…”
Section: Discussionmentioning
confidence: 99%
“…B10-insulin has a single amino acid substitution (histidine to aspartic acid) at [28][29][30] and chemical storage stability of this protein [30,31], as well as superior biological activity in terms of insulin receptor binding as tested in vitro [32][33][34][35]. A caveat is that B10-insulin has some mitogenic activity for several cell lines [36], primary cultures of smooth muscle cells [37], hepatocytes [38] and embryonic beta-islet cells [39]. At suprapharmacological doses B10-insulin induced adenocarcinomas in female rats [40], but establishing the relevance of this finding will require further studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this insulin analogue the histidine in position 10 of the B chain of the insulin molecule is replaced by aspartic acid [4]. The mutation of this insulin analogue has been shown to induce mitogenic effects [5][6][7], and according to the authors' [1] conclusion, could also be responsible for the observed liver transdifferentiation. Using the furin-cleavable insulin for the lentiviral transductions we detected a decrease in blood glucose concentration of STZ-diabetic rats from 22.3±3.4 to 15.6±2.1 mmol/l after 3 days and to 15.0±2.8 mmol/l after 30 days.…”
Section: Stz Streptozotocinmentioning
confidence: 99%